Acute segmental intestinal ischemia: diagnosis with spiral computed tomography. - Kailidou, E; Pikoulis, E; Katsiva, V; Papaconstantinou, I; Athanassopoulou, A; Gougoudi, E; Karavokyros, I; Leppaniemi, A; Tibishrani, M (JBR-BTR, 2006)
The purpose of this study was to examine the usefulness and the validity of spiral computerized tomography (CT) in assessing acute segmental intestinal ischemia. We present the spiral CT imaging findings in surgically proven cases of intestinal ischemia. 46 patients were admitted to our facility over a five-year period with suspicion of acute enteric ischemia. 34 were first examined with spiral CT and underwent surgery. In 24 of the 34 patients (sensitivity 70.6%), at least one imaging finding specific for segmental intestinal ischemia was recognised (true positive examinations). Spiral-CT examination demonstrated non-specific or normal findings in 7 out of 34 patients with proven intestinal ischemia (20.6% false negative studies). In conclusion, spiral CT can be used in the investigation of patients with suspected acute intestinal ischemia to confirm or suggest the diagnosis or exclude other potential diagnoses.
Keywords: Acute Disease; Adult; Aged; Aged, 80 and over; Female; Humans; Intestinal Diseases; Ischemia; Male; Middle Aged; Retrospective Studies; Tomography, Spiral Computed